2018
DOI: 10.3390/rs10122001
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Crop Evapotranspiration and Crop Coefficients over an Almond and Pistachio Orchard Throughout Remote Sensing

Abstract: In California, water is a perennial concern. As competition for water resources increases due to growth in population, California's tree nut farmers are committed to improving the efficiency of water used for food production. There is an imminent need to have reliable methods that provide information about the temporal and spatial variability of crop water requirements, which allow farmers to make irrigation decisions at field scale. This study focuses on estimating the actual evapotranspiration and crop coeff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 66 publications
2
34
0
Order By: Relevance
“…Almonds and pistachios are two high-value crops that have a reputation of being drought tolerant [37]. Previous studies have suggested that California needs 173,000 ha-m annually for almond and pistachio production [37]. The results of this study show the actual water use of almonds and pistachios to be closer to an annual average of 380,000 ha-m in raw water use and 250,000 ha-m in net irrigation once precipitation has been removed.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Almonds and pistachios are two high-value crops that have a reputation of being drought tolerant [37]. Previous studies have suggested that California needs 173,000 ha-m annually for almond and pistachio production [37]. The results of this study show the actual water use of almonds and pistachios to be closer to an annual average of 380,000 ha-m in raw water use and 250,000 ha-m in net irrigation once precipitation has been removed.…”
Section: Discussionmentioning
confidence: 57%
“…Almonds and pistachios are two high-value crops that have a reputation of being drought tolerant [37]. Previous studies have suggested that California needs 173,000 ha-m annually for almond and pistachio production [37].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this methodology is generic and appears as applicable on any large-enough group of mono-species urban vegetation, the main limitation being the resolution of the satellite used in the study. The phenology of mono-species grouped trees located in non-urban environments where mixed pixel problems can appear, such as in orchards [75,76] or woodlands/savannas [77][78][79], might be also studied with the proposed methodology.…”
Section: Methodology Hypotheses and Performancesmentioning
confidence: 99%
“…For decades, satellite remote sensing images have been the main data sources to integrate the FAO-56 for the estimation of crop ET. For example, Bellvert et al [19] used a dataset of the vegetation index (NDVI) derived from Landsat-8 to facilitate the estimation of the Kcb, and potential crop water use. However, the low spatial and temporal resolution of satellite data limits its further application in estimating ET within the field scale.…”
Section: Introductionmentioning
confidence: 99%